A study on the effect of injection moulding process parameters to the properties of injected parts - Sharifah Rafidah, Syed Hamid (2010)
Plastic has, quite literally, become the cornerstone of our society. We make so many things from plastic that it is hard to imagine what our lives would be like if it was never invented. The value of parameters should be correct and exact so that the good and quality of product can be produced. The objective for this project is to study the effects of injection parameters which are temperature, pressure and volume to the mechanical properties of the injected parts. Besides that, it also to determine the optimum amount of pressure, temperature and volume at the injection machine in producing document tray. In order to achieve the objectives, the scopes of studies are performed which is the study will be using a polymer material which is Samsung Starex® SD-0150GP High Impact Grade ABS. Besides that, only pressure, temperature and volume will be varied in this study while other parameter for instant clamping unit is fixed constant. The project can be divided into 4 stages. Firstly, is the preparation of the material. Then, injection moulding machine is used to produce document tray with the parameter that control the process which is temperature (220 oC, 230 oC, 240 oC), pressure (1675 bar, 1700 bar, 1725 bar) and volume (340 cm3, 350 cm3, 360 cm3). There are 27 samples produced by using full factorial method. After the samples are produced, there will be some testing for the samples such as mechanical testing such as tensile test and hardness test and physical testing such as density test. Lastly, analysis to determine the best and high quality of the samples was done. All the data obtained can be analyze and evaluate to produce the best optimum parameter for the injected part produce. As a result, the best injected part produced is sample number 10 which has good properties and optimum parameter is temperature at 230 oC, pressure at 1675 bar and volume at 340 cm3. It gives the low value of mass, low value of density, high of strength-to-weight ratio, high value of maximum strength and high value of hardness.